Strategic Management Practices in Islamic Higher Education Institutions: Strengthening Organizational Governance and Academic Quality - Said Maskur; Hasyamuddin Bin Othman (IQRAR: Jurnal Akuntansi, Manajemen & Ekonomi Syariah, 2025)
The background of this study stems from the need for Islamic higher education institutions to strengthen organizational governance and academic quality amidst globalization and digital transformation. The purpose of this research is to analyze strategic management practices in Islamic universities with particular emphasis on integrating Islamic values into governance and quality assurance. The research method employed a qualitative approach with a descriptive-analytical design through in-depth interviews, document review, and thematic analysis to obtain a comprehensive understanding. The findings reveal that strategic planning aligned with accountable governance principles and quality assurance mechanisms enhances academic quality and institutional legitimacy. The implication of this study highlights the necessity of harmonizing modern management practices with Islamic values to achieve sustainability and excellence in Islamic higher education